Knowledge, Attitude and Practice of Dietitians about Nutritional Supplements in Shiraz, 2014 - Afsane Ahmadi; Nasrin Nasimi; Farnoosh Fakoorziba; Javad Rasooli (Shiraz University of Medical Sciences, 2016)
Background: Due to the increasing global use of nutritional supplements, dietitians play a key role in raising consumer awareness and reducing supplementary side effects. Hence, determination of the states of knowledge, attitudes and practices of this group as to common dietary supplements is important. Methods: A list of all the dietitians employed in the health centers, nutrition clinics and private offices of Shiraz city was prepared; then, all the 36 qualified dietitians were referred to and the information of 25 dietitians was collected. To gather the data, we employed a 4-part questionnaire including demographic data and questions related to their knowledge, attitudes, and practices about prescribed dietary supplements. The knowledge scores of less than 50%, 50-75%, and over 75% were considered as low, medium, and good knowledge, respectively. And the classification of attitudes was determined based on quartile ranking. The data were statistically analyzed through SPSS, version19, using Chi-square and t-test statistical methods. Results: Most of the dietitians had moderate (80%) and low (20%) level of knowledge, while 100% of them had a positive attitude (3rd quartile) about the role of dietary supplements in health, side effects, and food interactions. The most common supplements recommended were those for anemia and growth of children. In this study, the dietitians who had higher level of knowledge significantly used nutritional journals to increase their awareness. Conclusion: Considering the key roles of dietitians and their knowledge, attitudes, and practices in the field of supplements and the results of the study, it appears that necessary measures should be taken to enhance the dietitians' knowledge.